Human milk extracellular vesicles preserve bronchial epithelial barrier integrity and reduce TLR3‐induced inflammation in vitro. Issue 9 (31st August 2022) - Karra, Nikita; Van Herwijnen, Martijn J. C.; Wauben, Marca H. M.; Swindle, Emily Jane; Morgan, Hywel
Abstract: Breast milk is essential for facilitating the growth and development of infants and for providing immune protection against viral infections in the infant's airways. Yet, regulation of inflammation by milk components may be needed to reduce immune pathology. While milk‐derived extracellular vesicles (EVs) are bestowed with immunomodulatory capacities, their role in bronchial epithelial barrier function and inflammation has not yet been examined. We hypothesised that during feeding, milk is not only ingested, but aerosols containing milk EVs are inhaled and locally delivered to the infant's airways to suppress aberrant inflammation. A bronchial epithelial model of viral infection was used to explore the direct effect of milk EVs on cellular barrier function and cytokine release during stimulation with a viral dsRNA analogue (Poly I:C). We demonstrate that milk EVs improved the dsRNA‐mediated decrease in ionic barrier integrity, limited tight junction reorganisation and reduced inflammatory cytokine production (IL‐6, IL‐8 and TNF‐α). This protective response was EV‐mediated, could be successfully titrated and exhibited a time‐dependent response. The results indicate that if EV‐containing milk aerosols are inhaled during feeding, this may lead to protection of the airway integrity from adverse inflammatory effects.